2011
DOI: 10.1002/ijc.26316
|View full text |Cite
|
Sign up to set email alerts
|

Administration of 6‐gingerol greatly enhances the number of tumor‐infiltrating lymphocytes in murine tumors

Abstract: Tumor-infiltrating lymphocytes (TILs) play critical roles in host antitumor immune responses. It is known that cancer patients with tumor-reactive lymphocyte infiltration in their tumors have better prognoses, while patients with tumors infiltrated by immunosuppressive cells have worse prognoses. We found that administration of 6-gingerol, which is a component of ginger, inhibited tumor growth in several types of murine tumors, such as B16F1 melanomas, Renca renal cell carcinomas and CT26 colon carcinomas, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Down-regulation of the overexpression of NFkb, AKT and Bcl2 genes in cancer cells. IC50 values for 24 and 48 h treatment were found to be 126 and 114 lg/mL, 50 = 1.1 lg/mL for 6-SG and 4.5 lg/mL for 10-GN)Kim et al (2008) Mouse ovarian cancer cell lines, C1(genotype: p53 À/À , c-myc, K-ras) and C2 (genotype: p53 À/À , of PPARc transcriptional activity, suppression of NFjB activity and induction of apoptosis in cancer cells at 100 lMTan et al (2013) HCT15 (human colon cancer cells) 6-SG, 10-GN Cytotoxic (ED 50 = 1.76 lg/mL for 6-SG and 6.57 lg/mL for 10-GN) Kim et al (2008) HCT 116 (human colon carcinoma cells) 4-and 6-SG Apoptosis by inducing aberrant mitosis through the attenuation of cell cycle and spindle assembly checkpoint proteins at 100 lM Gan et al (2011) 6-GN and 6-SG Inhibition of growth of cancer cells (IC 50 8 lM for 6-SG and 150 lM for 6cancer cell growth (IC 50 = 160.4 lM) Lv et al (2012) COLO 205 (human colon cancer cells) 6-GN Inhibition of growth and induced apoptosis in cancer cells due to the modulation of mitochondrial functions through regulation of ROS Pan et al an early signalling effect in cancer cells by increasing intracellular calcium concentration, [Ca 2+ ]i Yi et al (2009) LoVo (human colon cancer cells) 6-GN Reduced cell viability of cancer cells by inducing G2/M phase arrest with slight effect on the sub-G1 phase Lin et al Suppressed the expression of cyclin D1, while enhancing that of NAG-1 apoptosis in cancer cells stimulated through the upregulation of NAG-1 and the arrest of the G1 cell cycle through downregulation of cyclin D1 Lee et al (2008b) Lee et al (2008b) CT26 (mouse colon carcinoma) 6-GN Increased tumour-infiltrating lymphocytes in mouse tumours (in vivo) at 3 lg/mL orally it caused massive infiltration of CD4 and CD8 T-cells and B220 + B-cells, but reduced the number of CD4 + Foxp3 + regulatory T-cells in tumour-bearing mice Ju et al (2012) Lung cancer A-549 (human lung cancer cells) 6-SG, 10-GN Cytotoxic (ED 50 = 1.47 lg/mL for 6-SG and 5.09 lg/mL for 10-GN) Kim et al (2008) H-1299 (human lung cancer cells) 6-GN and 6-SG Inhibition of growth of cancer cells (IC 50 8 lM for 6-SG and 150 lM for 6-GN) Sang et al (2009) 6-GN Cytotoxic against cancer cells (IC 50 = 136.73 lM) Lv et al (2012) Skin cancer SK-MEL-2 (human skin cancer cells) 6-SG, 10-GN Cytotoxic (ED 50 = 1.1 lg/mL for 6-SG and 5.92 lg/mL for 10-GN) Kim et al (2008) B16F1 (mouse skin melanoma) 6-GN Increased tumour-infiltrating lymphocytes in mouse tumours (in vivo).It caused massive infiltration of CD4 and CD8 T-cells and B220 + B-cells, but reduced the number of CD4 + Foxp3 + regulatory T-cells in tumour-bearing miceJu et al (2012) …”
mentioning
confidence: 92%
“…Down-regulation of the overexpression of NFkb, AKT and Bcl2 genes in cancer cells. IC50 values for 24 and 48 h treatment were found to be 126 and 114 lg/mL, 50 = 1.1 lg/mL for 6-SG and 4.5 lg/mL for 10-GN)Kim et al (2008) Mouse ovarian cancer cell lines, C1(genotype: p53 À/À , c-myc, K-ras) and C2 (genotype: p53 À/À , of PPARc transcriptional activity, suppression of NFjB activity and induction of apoptosis in cancer cells at 100 lMTan et al (2013) HCT15 (human colon cancer cells) 6-SG, 10-GN Cytotoxic (ED 50 = 1.76 lg/mL for 6-SG and 6.57 lg/mL for 10-GN) Kim et al (2008) HCT 116 (human colon carcinoma cells) 4-and 6-SG Apoptosis by inducing aberrant mitosis through the attenuation of cell cycle and spindle assembly checkpoint proteins at 100 lM Gan et al (2011) 6-GN and 6-SG Inhibition of growth of cancer cells (IC 50 8 lM for 6-SG and 150 lM for 6cancer cell growth (IC 50 = 160.4 lM) Lv et al (2012) COLO 205 (human colon cancer cells) 6-GN Inhibition of growth and induced apoptosis in cancer cells due to the modulation of mitochondrial functions through regulation of ROS Pan et al an early signalling effect in cancer cells by increasing intracellular calcium concentration, [Ca 2+ ]i Yi et al (2009) LoVo (human colon cancer cells) 6-GN Reduced cell viability of cancer cells by inducing G2/M phase arrest with slight effect on the sub-G1 phase Lin et al Suppressed the expression of cyclin D1, while enhancing that of NAG-1 apoptosis in cancer cells stimulated through the upregulation of NAG-1 and the arrest of the G1 cell cycle through downregulation of cyclin D1 Lee et al (2008b) Lee et al (2008b) CT26 (mouse colon carcinoma) 6-GN Increased tumour-infiltrating lymphocytes in mouse tumours (in vivo) at 3 lg/mL orally it caused massive infiltration of CD4 and CD8 T-cells and B220 + B-cells, but reduced the number of CD4 + Foxp3 + regulatory T-cells in tumour-bearing mice Ju et al (2012) Lung cancer A-549 (human lung cancer cells) 6-SG, 10-GN Cytotoxic (ED 50 = 1.47 lg/mL for 6-SG and 5.09 lg/mL for 10-GN) Kim et al (2008) H-1299 (human lung cancer cells) 6-GN and 6-SG Inhibition of growth of cancer cells (IC 50 8 lM for 6-SG and 150 lM for 6-GN) Sang et al (2009) 6-GN Cytotoxic against cancer cells (IC 50 = 136.73 lM) Lv et al (2012) Skin cancer SK-MEL-2 (human skin cancer cells) 6-SG, 10-GN Cytotoxic (ED 50 = 1.1 lg/mL for 6-SG and 5.92 lg/mL for 10-GN) Kim et al (2008) B16F1 (mouse skin melanoma) 6-GN Increased tumour-infiltrating lymphocytes in mouse tumours (in vivo).It caused massive infiltration of CD4 and CD8 T-cells and B220 + B-cells, but reduced the number of CD4 + Foxp3 + regulatory T-cells in tumour-bearing miceJu et al (2012) …”
mentioning
confidence: 92%
“…It could inhibit the metastasis of MDA-MB-231 breast cancer cells and induce apoptosis in LNCaP prostate cancer cells [9], [10]. Administration of [6]-gingerol inhibited the growth of several types of murine tumors such as melanomas, renal cell carcinomas and colon carcinomas by enhancing the infiltrations of tumor-infiltrating lymphocytes CD4 and CD8 T-cells and B220 + B-cells [11]. [6]-gingerol was also shown to inhibit the progression of phorbol ester-induced skin tumor in ICR mice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Kim and co-workers found that 6-gingerol inhibited the proliferation and tube formation of primary cultured human endothelial cells in response to vascular endothelial growth factor (VEGF), caused cell cycle arrest in the G1 phase, and suppressed experimental metastases in tumor-bearing mice (4). A more recent study reported that administration of 6-gingerol greatly enhanced the number of tumor-infiltrating lymphocytes in murine tumors (5). …”
Section: Introductionmentioning
confidence: 99%